TRANSITION BIAS AND NEUTRAL SELECTION DRIVE THE EVOLUTION OF THE POLYKETIDE SYNTHASE GENE IN ASPERGILLUS SECTION NIGRI - THOMAS, Benjamin Thoha; Coker, Mercy Olawunmi; Taiwo, Olumide Simon; Thomas, Abiodun Noel; Popoola, Omolara Dorcas (Polish Journal of Natural Sciences, 2025)
The significance of the polyketide synthase (pks) gene in the biosynthesis of ochratoxin A in Aspergillus section Nigri has been well reported. However, factors driving the evolution of this gene in black aspergilli are seldom studied. This study, was therefore, aimed at investigating these factors as a means to understanding how to circumvent their wide epidemiological coverage in the nearest future. To achieve this, a total of one thousand cassava powders (Lafun) were collected from the four geopolitical zones of Ogun State, Nigeria and processed for black aspergilli using standard mycological procedures. The isolated organisms were subsequently characterised phenotypically, followed by screening for ochratoxin A production and sequencing of the pks gene associated with its biosynthesis. The sequenced pks genes were used for mutation discovery, estimation of selection, substitution pattern and phylogenetic analyses. The results revealed a total of 279 black aspergilli, distributed as follows: Aspergillus niger – 88 (8.8%), A. welwitschiae – 82 (8.2%), A. carbonarius – 56 (5.6%), and A. aculeatus – 47 (4.7%). Among these, 18 strains, comprising 6 A. niger, 3 A. aculeatus, 7 A. carbonarius, and 2 A. welwitschiae were identified as ochratoxigenic based on both phenotypic characterization and molecular amplification of the pks gene. The quantitative measurements of their ochratoxins ranged from 9.12–11.08 for Aspergillus aculeatus through 10.52–12.74 and 19.39–23.61 for Aspergillus carbonarius and Aspergillus niger to 23.88–27.02 for Aspergillus welwitschiae. All the ochratoxigenic Aspergillus welwitschiae, Aspergillus aculeatus and Aspergillus niger were clustered together on the phylogenetic tree. The maximum likelihood estimate of the transition-transversion bias of the pks genes of black aspergilli depicts that the number of proteins in the data set of the pks genes, the transition-transversion bias ratio and the maximum likelihood estimate were 2215 bp, 1.01 and –13279.996 respectively. The maximum composite likelihood estimates of the pattern of nucleotide substitution revealed frequent transitions than transversions in the polyketide synthase genes of Aspergillus section Nigri. The results showed that A/G and T/C transition were more frequent than C/T and G/A while the codon-based Fisher’s exact test analysis of selection, the Codon-based Z-test of neutral evolution and the results from Tajima’s Neutrality Test connotes significant bias for neutral evolution (p < 0.05). The above results suggest that transition and neutral selection drive the evolution of the pks gene of Aspergillus section Nigri.